In vitro cultured lung cancer cells are not suitable for animal-based breath biomarker detection. (11th February 2015) - Schallschmidt, Kristin; Becker, Roland; Zwaka, Hanna; Menzel, Randolf; Johnen, Dorothea; Fischer-Tenhagen, Carola; Rolff, Jana; Nehls, Irene
Abstract: In vitro cultured lung cancer cell lines were investigated regarding the possible identification of volatile organic compounds as potential biomarkers. Gas samples from the headspace of pure culture medium and from the cultures of human lung adenocarcinoma cell lines A549 and Lu7466 were exposed to polypropylene fleece in order to absorb odour components. Sniffer dogs were trained with loaded fleeces of both cell lines, and honey bees were trained with fleeces exposed to A549. Afterwards, their ability to distinguish between cell-free culture medium odour and lung cancer cell odour was tested. Neither bees nor dogs were able to discriminate between odours from the cancer cell cultures and the pure culture medium. Solid phase micro extraction followed by gas chromatography with mass selective detection produced profiles of volatiles from the headspace offered to the animals. The profiles from the cell lines were largely similar; distinct differences were based on the decrease of volatile culture medium components due to the cells' metabolic activity. In summary, cultured lung cancer cell lines do not produce any biomarkers recognizable by animals or gas chromatographic analysis.